Understandable statistics concepts and methods - Brase, Charles Henry; Brase, Corrinne Pellillo (Cengage Learning, 2015)
Provides guidance and informal advice while showing the links between statistics and the world. To reinforce this approach - and make the material interesting as well as easier to understand, this book integrates real-life data from a variety of sources, including journals, periodicals, newspapers, and the Internet